A terrifying taste of short & shivery : thirty creepy tales - San Souci, Robert D. (Delacorte Press, 1998)
A collection of scary traditional tales from all over the world, including "Apparitions" from Germany, "The Hundredth Skull" from Ohio, and "The Ogre's Arm" from Japan.